Na rob resolucijskim smernicam o sodelovanju javnosti pri pripravi predpisov - Igličar, Albin (Pravni letopis, 2010)
Rational elements of public opinion often step aside as the public opinion changes into moral evaluation of a group of facts. When values enter the subject matter of public opinion, however, this form of consciousness obtains a normative nature, as well. Side by side with values as collective ideas about the desired characteristics and goods, the normative subject matter is filled with numerous social rules, from common, professional or political rules to statutory and/or legal rules. From this point of view, on one hand, legal rules are determined, upon their origin, by the subject matter of public opinion, and on the other hand, these rules themselves co-create the public opinion. Through public opinion, legal rules enter the social consciousness and the general legal culture of a certain global society.
Keywords: javno mnenje; javnost; predpisi; sodelovanje; zakonodajni postopek